2014
DOI: 10.1177/1040638714559026
|View full text |Cite
|
Sign up to set email alerts
|

Enteric disease in postweaned beef calves associated with Bovine coronavirus clade 2

Abstract: Bovine coronavirus (BoCV; Betacoronavirus 1) infections are associated with varied clinical presentations including neonatal diarrhea, winter dysentery in dairy cattle, and respiratory disease in various ages of cattle. The current report presents information on BoCV infections associated with enteric disease of postweaned beef cattle in Oklahoma. In 3 separate accessions from a single herd, 1 in 2012 and 2 in 2013, calves were observed with bloody diarrhea. One calf in 2012 died and was necropsied, and 2 calv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 7 publications
0
16
0
4
Order By: Relevance
“…Although only one serotype of BCoV has been identified, there is increasing evidence of divergence of recent isolates from the historical reference strain used for most vaccine formulations (Mebus strain) [18,42,43]. In this regard, the strains detected in this study are divergent from the Mebus strain, as observed in the phylogenetic analysis, and nine amino acid differences were observed between the Uruguayan strains and Mebus.…”
Section: Discussionmentioning
confidence: 52%
“…Although only one serotype of BCoV has been identified, there is increasing evidence of divergence of recent isolates from the historical reference strain used for most vaccine formulations (Mebus strain) [18,42,43]. In this regard, the strains detected in this study are divergent from the Mebus strain, as observed in the phylogenetic analysis, and nine amino acid differences were observed between the Uruguayan strains and Mebus.…”
Section: Discussionmentioning
confidence: 52%
“…38 Similar results have been reported in Europe and Asia . In 2012, the BCoV clade 2 strain was recovered from postweaned calves (6–7 months) suffering of severe enteritis with bloody diarrhea; the authors of that study suggested that this clinical syndrome caused by BCoV clade 2 should be added to the already known syndromes caused by BCoV . The results of these studies suggest that current BCoV strains circulating in worldwide are diverging from the prototype BCoV isolated in earlier studies and used in vaccines .…”
Section: Discussionmentioning
confidence: 53%
“…The results of these studies suggest that current BCoV strains circulating in worldwide are diverging from the prototype BCoV isolated in earlier studies and used in vaccines . This can result in the emergency of new clinical syndromes, outbreaks of enteric diseases with higher morbidity and case fatality (similar to the one described in this study), increased detection rates of BCoV in nasal and fecal samples of healthy and ill calves, and the lack of efficacy vaccination protocols . Future studies should focus on investigating the biological, antigenical, and genomical characteristic of BCoV circulating in Canada.…”
Section: Discussionmentioning
confidence: 54%
“…The same phenomenon might occur with certain strains of other countries such as Brazil. However, challenge studies in validated animal models are required to ascertain the correlation between strain-specific antigenic distances and efficiency of vaccine protection in cattle infected with the current Brazilian field strains of BCoV (Fulton et al, 2015).…”
Section: Discussionmentioning
confidence: 99%